Analisis Pendapatan Objek Wisata dan Kontribusinya Terhadap Pendapatan Asli Daerah Kabupaten Bone Bolango Tahun 2020-2022 - Sri Mulyani Ahmad; Ronald S. Badu; Victorson Taruh (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the level of income generated by tourist attractions in Bone Bolango Regency and to analyze the extent of the contribution of tourist attraction income levies to Regional Original Income in Bone Bolango Regency. The data source used in this research is secondary data sourced from time series data over a three year period, namely from 2020 to 2022. This research utilizes a documentation method that involves the use of secondary data, with a range of observations from 2020 to 2022. The secondary data used used comes from a report prepared by a related institution. The data analysis technique used in this research is quantitative descriptive analysis, namely by using the calculation of tourist attraction income and calculating the contribution of tourism levies to local original income using the Value Formatting method. The research results show that (1) After conducting research over the last three years, income from the Bone Bolango Regency tourist attraction has experienced stable growth. Total income during this period reached impressive figures, with an average amount during 2020 to 2022 of IDR. 674,056,515. This success reflects efforts to manage and increase the attractiveness of tourist destinations in Bone Bolango Regency. (2) After conducting research over the last three years, the contribution of tourism sector levies to the original regional income of Bone Bolango Regency has experienced fluctuations. The tourism sector managed to achieve an excellent contribution level with an average of 58.43% during 2020 to 2022. This success not only reflects the attractiveness of the Bone Bolango Regency tourist destination, but also the effectiveness of management strategies and positive engagement.